Pengembangan Soal Matematika Model PISA Konten Bilangan untuk Mengetahui Kemampuan Literasi Matematika Siswa - Putra, Yudi Yunika; Zulkardi, Zulkardi; Hartono, Yusuf (Universitas Hamzanwadi, 2016)
The aims of the research are (1) to product content quantity PISA-like problems which validity and practicality, and (2) to know the potential effect of the content quantity mathematical PISA-like problems for mathematic literacy ability. The subjects of the research are student SMP AR-RAIHAN Bandar Lampung. The research method used is development research which consist of two stages, they are preliminary and prototyping. In the preliminary stage have been done analysis for research subject, curricula, analysis for content and manufacture of instruments. Meanwhile, in prototyping stage used formative evaluation which includes : self evaluation, one-to-one,expert review, small group, and field test. The data collection techniques used in the research were walk through (expert review stage) for knowing the validity of the content, construct, and language. Analysis one-to-one stage, small group stage, and quetionaire (small group stage) for knowing the practicality; test results, quetionaire, and interview (field test stage) for knowing potential effect. Based on the data analysis of research, it can be concluded that: 1) this research produced 4 items of content quantity PISA like mathematical problems which are valid and practice.The problems declared valid based on comments about content, construct, and language by experts and analysis in validity criteria; otherwise practical based on the student argumentation such as the problems can be understood by student and can be implementation properly; and 2) Of content quantity PISA like mathematical problems has potential effect on student. Based test result and questionnaire all based mathematical ability (KDM) be used student for answer questions.